L-Cysteine (3-Nitrophenyl)methyl Ester Hydrochloride: A New Chiral Reagent in the Sugar Analysis - De Marino, Simona; Festa, Carmen; Iorizzi, Maria; Zollo, Franco (Letters in Organic Chemistry, 2017)
Background: Several GC and HPLC methods have been proposed for the separation of aldose enantiomers. Method: We developed a general HPLC method for the discrimination of (D,L)-monosaccharide components from natural products. The reaction involves the preparation of L-cysteine (3-nitrophenyl) methyl ester hydrochloride, which reacts with aldoses leading to thiazolidine derivatives. Results: Direct HPLC analysis with reversed-phase column and UV detection, discriminated enantiomeric D- and L-monosaccharides in a highly sensitive manner. Conclusion: This method was applied for the determination of the absolute configurations of monosaccharides in the natural poliumoside B, a tetraglycoside obtained from Teucrium polium.
Keywords: enantioseparation